EDUKASI PERTOLONGAN PERTAMA DENGAN BALUTAN CEDERA PADA PELAJAR DI SMP YAYASAN PERGURUAN WASHLIYANI MEDAN BESAR - Pangaribuan, Resmi; Khairani, Ade Irma; Gea, Handerman Vitu; Juwita, Arni; Hasudungan, Richard; Purba, Josia; Simorangkir, Nadya (MAJU : Indonesian Journal of Community Empowerment, 2025)
School students are a group at high risk of emergency incidents, because there are many possibilities that can happen to this group. In addition, children spend a lot of time at school and are at greater risk of injury. The implementation of this community service activity uses several stages. The expected product of this activity is understanding of the school community through situation analysis, expert discussion, solution design, implementation of activities in the form of socialization and health education, as well as post-activity assistance. After conducting education during community service activities regarding education on extremity bandages at the Washliyani Education Foundation Middle School in Medan Besar Village, Medan Labuhan District, it succeeded in increasing the participants' understanding and providing strategies to overcome the impact. Where the level of knowledge from pre-education to post-education has increased to good knowledge (79%). With this activity, students become aware of the need to maintain health and the ability to provide assistance with bandages. This activity needs to be carried out more often, especially for all elements of society so that they understand more about accident relief by applying bandages.